Use of social audits to examine unofficial payments in government health services: experience in South Asia, Africa, and Europe - Paredes-Solís Sergio; Andersson Neil; Ledogar Robert J; Cockcroft Anne (BMC, 2011)
Abstract Background Unofficial payments in health services around the world are widespread and as varied as the health systems in which they occur. We reviewed the main lessons from social audits of petty corruption in health services in South Asia (Bangladesh, Pakistan), Africa (Uganda and South Africa) and Europe (Baltic States). Methods The social audits varied in purpose and scope. All covered representative sample communities and involved household interviews, focus group discussions, institutional reviews of health facilities, interviews with service providers and discussions with health authorities. Most audits questioned households about views on health services, perceived corruption in the services, and use of government and other health services. Questions to service users asked about making official and unofficial payments, amounts paid, service delivery indicators, and satisfaction with the service. Results Contextual differences between the countries affected the forms of petty corruption and factors related to it. Most households in all countries held negative views about government health services and many perceived these services as corrupt. There was little evidence that better off service users were more likely to make an unofficial payment, or that making such a payment was associated with better or quicker service; those who paid unofficially to health care workers were not more satisfied with the service. In South Asia, where we conducted repeated social audits, only a minority of households chose to use government health services and their use declined over time in favour of other providers. Focus groups indicated that reasons for avoiding government health services included the need to pay for supposedly free services and the non-availability of medicines in facilities, often perceived as due to diversion of the supplied medicines. Conclusions Unofficial expenses for medical care represent a disproportionate cost for vulnerable families; the very people who need to make use of supposedly free government services, and are a barrier to the use of these services. Patient dissatisfaction due to petty corruption may contribute to abandonment of government health services. The social audits informed plans for tackling corruption in health services.